Improvement the production of cytotoxic metabolites by Streptomyces griseus KJ623766 - Ahmed S. Abu Zaid; Khaled Aboshanab; Mahmoud A. Yassien; Nadia A. Hassouna (Ain Shams University, 2017)
The cell-free culture supernatant (CFCS) obtained from Streptomyces (S.) grisues (accession codeKJ623766) fermentation, locally isolated Streptomyces strains from Egyptian soil sample, showed potent cytotoxic activity against Caco2 cell line. Fermentation was carried out in a 14 L laboratory fermenter, under optimum conditions of 28 °C, 200 rpm, 5 standard liters per minute (SLPM) aeration, 2 bar airflow pressure and uncontrolled pH. After 72 h of incubation, the cell-free culture supernatant (CFCS) was collected and extracted using ethyl acetate (1:1, v/v) at pH 7.0. Using 3-(4,5-dimethylthazol-2-yl)-2,5-diphenyl tetrazolium-bromide (MTT) assay, the ethyl acetate extract showed potential cytotoxic activity against Caco2 with CD50of 14 µg/mL. This showed an increase in cytotoxic activity by about 1.6 folds when compared to results obtained from shake flask (CD5022 µg/mL). Production improvement of cytotoxic activity was carried out also by genetic manipulation using a dose of 4 KiloGray (KGy) of gamma radiation. Fifteen out of forty-seven mutants showed higher potential cytotoxic activities when compared to that of the wild-type strain of S.griseus KJ623766. Mutants G31, G44, and G45 showed the most potent cytotoxic activities where they exhibited about 7 folds increase in potential cytotoxic activity with CD50 of 3.2 ±0.2, 2.9 ±0.1 and 3.25 ±0.43 µg/mL, respectively.